Objective and efficient inference for couplings in neuronal network*This article is an updated version of: Terada Y, Obuchi T, Isomura T and Kabashima Y 2018 Objective and efficient inference for couplings in neuronal networks Advances in Neural Information Processing Systems 31 ed S Bengio, H Wallach, H Larochelle, K Grauman, N Cesa-Bianchi and R Garnett (Red Hook, NY: Curran Associates, Inc) pp 4971–4980. (20th December 2019) - Terada, Yu; Obuchi, Tomoyuki; Isomura, Takuya; Kabashima, Yoshiyuki
Abstract: Inferring directional couplings from the spike data of networks is desired in various scientific fields such as neuroscience. Here, we apply a recently proposed objective procedure to the spike data obtained from the Hodgkin–Huxley type models and in vitro neuronal networks cultured in a circular structure. As a result, we succeed in reconstructing synaptic connections accurately from the evoked activity as well as the spontaneous one. To obtain the results, we invent an analytic formula approximately implementing a method of screening relevant couplings. This significantly reduces the computational cost of the screening method employed in the proposed objective procedure, making it possible to treat large-size systems as in this study.